Analysis Using the Weibull Distribution in the Evaluation of the Quality of Red Ceramic Incorporated with Sugar Cane Bagasse Ash (International Journal of Geoscience, Engineering and Technology, 2022)
The quality of incorporate red ceramic with 10% sugar cane bagasse ash using the Weibull distribution is investigated. Emphasis was given the influence of the grain size of the sugar cane bagasse ash in the resistance for diametrical compression. Three different sugar cane bagasse ash grain sizes were used: 150 µm (100 mesh), 75 µm (200 mesh) and 44 µm (325 mesh). Samples were prepared by uniaxial pressing and sintered at 950 ºC. The following Weibull parameters were obtained: Weibull module (m), characteristic resistance (σ0) and correlation coefficient (R). The results indicated that the red ceramic MC 325 presented better quality in terms of the mechanical behavior determinate through resistance for diametrical compression.